2021
DOI: 10.1038/s41590-021-00911-7
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis and controlled malaria infection in Europeans and Africans elucidate naturally acquired immunity

Abstract: Controlled human infections provide opportunities to study the interaction between the immune system and malaria parasites, which is essential for vaccine development. Here, we compared immune signatures of malaria-naive Europeans and of Africans with lifelong malaria exposure using mass cytometry, RNA sequencing and data integration, before and 5 and 11 days after venous inoculation with Plasmodium falciparum sporozoites. We observed differences in immune cell populations, antigen-specific responses and gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 67 publications
(79 reference statements)
5
30
0
Order By: Relevance
“…As well as providing a platform for evaluation of candidate vaccines, a human-challenge model of S. pyogenes infection offers the unique opportunity to interrogate the dynamic host immune response to infection using samples collected before, during, and after development of disease. Human-challenge models have been established for other infectious pathogens such as Vibrio cholerae, Salmonella Typhi and Paratyphi, Streptococcus pneumoniae, respiratory syncytial virus and malaria, and have enormous potential to successfully guide vaccine development [11][12][13][14][15] . Recently, a new human-challenge model of S. pyogenes pharyngitis in healthy adults was established in an initial dose-finding clinical trial, after an extensive effort to select and characterise a challenge strain and develop a study protocol to protect participants and promote the model's clinical relevance [16][17][18] .…”
mentioning
confidence: 99%
“…As well as providing a platform for evaluation of candidate vaccines, a human-challenge model of S. pyogenes infection offers the unique opportunity to interrogate the dynamic host immune response to infection using samples collected before, during, and after development of disease. Human-challenge models have been established for other infectious pathogens such as Vibrio cholerae, Salmonella Typhi and Paratyphi, Streptococcus pneumoniae, respiratory syncytial virus and malaria, and have enormous potential to successfully guide vaccine development [11][12][13][14][15] . Recently, a new human-challenge model of S. pyogenes pharyngitis in healthy adults was established in an initial dose-finding clinical trial, after an extensive effort to select and characterise a challenge strain and develop a study protocol to protect participants and promote the model's clinical relevance [16][17][18] .…”
mentioning
confidence: 99%
“…On the other hand, another explanation relying on the marked CD4 + T cell activity at baseline may provide a scenario where the saturated activation of T cells and/ or previous activation of dendritic cells (DCs) before vaccination may reflect the influence of the frequent natural exposure to P. falciparum [35]. It has also been shown that elevated levels of CD161 + CD4 + T cells and malaria-specific IFN-γ-production predicted protection against CHMI [36].…”
Section: Discussionmentioning
confidence: 99%
“…The targeted antigens included several biomarkers of exposure [42] and well-described malaria vaccine candidates. Associations between antibody breadth and protection, as well as responses to specific malaria antigens and protection, have been described in malaria-naïve volunteers immunized with sporozoites under chemoprophylaxis [36,43]. There, either patterns or specific antigens were associated with protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, Plasmodium falciparum (P. falciparum) and Plasmodium vivax (P. vivax) are more widely distributed [3]. In sub-Saharan Africa, P. falciparum is the cause of most malaria cases while P. vivax is reported to cause most of the malaria cases in Asia; P. falciparum cause more fatal disease [4].…”
Section: Introduction 11 Malaria -A Global Infectious Diseasementioning
confidence: 99%